Multilocus phylogenetic assessment of the taxonomic status of the Turkish endemic Astrantia maxima subsp. haradjianii (Saniculoideae) - Doğru-Koca, Asli (Phytotaxa, 2025)
Astrantia is a small genus within the family Apiaceae. Among its 15 recognized taxa, Astrantia maxima subsp. haradjianii is a Turkish endemic that has not previously been included in any phylogenetic analyses. This study aimed to evaluate the taxonomic status of subsp. haradjianii, which, despite exhibiting clear morphological distinctions, such as smaller umbel size, has been classified as a subspecies. To investigate its potential elevation to species rank, multiple populations of both subspecies were analyzed using phylogenetic methods based on nuclear ribosomal (complete internal transcribed spacer region) and combined chloroplast (rps16, rpl16, matK, rbcL, psbA-trnH, trnL, trnL-trnF, and rps16-trnK) DNA sequences. The phylogenetic reconstruction revealed that the subsp. maxima and subsp. haradjianii are closely related yet separated by distinct genetic divergence, which is particularly evident in the chloroplast dataset. Based on this phylogenetic evidence, the current subspecific classification of A. maxima subsp. haradjianii was reconsidered, and its elevation to species rank is proposed. Furthermore, a lectotype was designated for the name Astrantia haradjianii.